AL-SHAFI-THE FOUNDER OF MUSLIM LEGAL DOCTRINE. THE FORMATION OF USUL AL-FIQH (Journal of Oriental Studies, 2024)
Muslim law, fiqh, is the religious and legal sphere of Islam, which defines the rules of legal behavior of Muslims, permits or prohibits them from this or that action. Fiqh in translation means "deep understanding", and the term "fiqh" in Armenian can be interpreted as a collection of norms interpreting and explaining Islamic law, "Islamic law" or Muslim teaching on the rules of conduct, that, in a broader sense, means Muslim law. Fiqh is the legal branch of Islam about correctly understanding the nature of intentions. The confirmation of the use of the word fiqh in this sense can be found in the following words of the Prophet Muhammad: "To whom Allah wills good, He also grants the ability to understand religion in a true way." Al-Shafi'i had a significant contribution to the development of Islamic law. The theory of "Uṣūl al-fiqh" without fundamental changes is also accepted by modern Muslim jurisprudence and is considered as the theoretical foundation of fiqh.
Keywords: Fiqh; Quran; Sunnah; Ahl Ar-Rai; hl AL-Hadis; Ijma; Qiyas